Industry Perceptions of TVET Graduates’ Competencies in Malaysia: A Case Study in the Automotive Sector - Ahmad Firdaus; Muhammad Aiman (PT. Berkah Smart Academica, 2024)
This study aims to explore industry perceptions of the competencies of Technical and Vocational Education and Training (TVET) graduates in Malaysia, with a particular focus on the automotive sector. A qualitative approach using a case study design was employed, involving semi-structured interviews with representatives from the automotive industry. The findings indicate that TVET graduates generally possess basic technical skills that are relevant to industry needs, especially in automotive operations and maintenance. However, the industry highlighted deficiencies in soft skills such as communication, work discipline, and professional attitudes. In addition, the level of graduates’ readiness for the real working environment varies depending on the quality of industrial training exposure and the institutions attended. The study suggests that stronger collaboration between TVET institutions and the automotive industry is necessary to ensure better alignment of curricula and training with current industry demands. The findings are expected to contribute to policy improvement and the enhancement of TVET implementation in Malaysia.